Генетски аспекти на делинквентното и криминалното однесување - Трајковски, Владимир (Faculty of Philosophy, UKIM, Skopje, Macedonia, 2004)
Development of criminology, especially with large impact of psychology and psychiatry in studying the offenders of norms in the society, actual question is meaning of genetic factors in criminology. The aim of the article is to describe genetically determinants of delinquent and criminal behavior. This article contains cross-section of big number of world studies, which analyze the genetic aspects of delinquent and criminal behavior. The chromosome aberrations, especially those involving X and Y-chromosomes, provide a model to show how genetic variability and environment may interact in producing a psychological phenotype. Analyzes of cited studies for the impact of genetic factor in genesis of delinquent and criminal behavior can't confirm it predominance, but the responsibility is equal between genetic predisposition in high correlation with environmental factors.
Genetic Aspects of Delinquent and Criminal Behavior
Keywords: генетски, делинквентно, криминално, антисоцијално, однесување, конкордантност